2016
DOI: 10.1155/2016/8417190
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of Soluble HLA-G in Chronic Left Ventricular Systolic Dysfunction

Abstract: Left ventricular systolic dysfunction (LVSD) defined by ejection fraction (EF) <40% is common, serious but treatable, and correct diagnosis is the cornerstone of effective treatment. Biomarkers may help to diagnose LVSD and give insight into the pathophysiology. The immune system is activated in LVSD, and the immunomodulatory molecule human leukocyte antigen-G (HLA-G) may be involved. The primary aim was to measure soluble HLA-G (sHLA-G) in the blood in different stages of LVSD (<30% and 30–40%), in the midran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Moreover, diseases in which RAS is activated (i.e. heart failure with reduced ejection fraction and hypertension) present with increased soluble HLA-G (27,28).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, diseases in which RAS is activated (i.e. heart failure with reduced ejection fraction and hypertension) present with increased soluble HLA-G (27,28).…”
Section: Discussionmentioning
confidence: 99%
“…showed a higher secretion of sHLA-G in CD patients [ 48 ]; no significant difference was detected between plasma levels of SLE patients and control group, although a reduced plasma concentration of sHLA-G was observed when the patients were stratified according to clinical manifestations [ 49 ]. Regarding CVDs, higher levels of circulating sHLA-G were observed in heart transplantation [ 50 ], whereas there are no data about sHLA-G concentrations in CHD patients. In our study, for all subjects, plasma levels of sHLA-G were evaluated, but a not statistically significant difference of sHLA-G level was detected into CS group compared to NCS individuals (p = 0.09).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been demonstrated that PHF8 is reduced in human failing hearts and required to attenuate cardiac hypertrophy upon pressure overload . Accordingly, soluble HLA‐G was found to be upregulated in the blood of patients with heart failure or with chronic left ventricular systolic dysfunction : It is therefore tempting to speculate that PHF8 might also regulate HLA‐G alternative splicing during heart failure.…”
Section: Discussionmentioning
confidence: 99%